A numerical/experimental study on the induction heating of adhesives for composite materials bonding. (June 2018) - Riccio, A.; Russo, A.; Raimondo, A.; Cirillo, P.; Caraviello, A.
Graphical abstract: Abstract: In this paper, the bonding of carbon fiber reinforced polymer (CFRP) components by induction heating has been numerically simulated. Being the induction heating bonding phenomenon characterised by an intrinsic multi-physical nature, three different numerical models taking into account, respectively, electromagnetic, thermic and structural aspects, have been introduced and applied to a stiffened composite panel to predict the stringer/skin interface characteristics. The electromagnetic model evaluates the energy loss due to the Joule effect while the thermal model is used to calculate the temperature distribution within the adhesive layer between skin and stringer. Then the structural model predicts the ultimate failure load of the stiffened panel taking into account the degree of cure of the adhesive depending on the temperature distribution at interface between skin and stringers by means of an experimentally determined degradation law. The overall developed numerical methodology has been preliminary validated by comparisons with experimental data in terms of adhesive temperature as a function of time on rectangular composite coupons. Finally, a sensitivity analysis has been performed to evaluate the effects of the geometrical parameters of the stiffened composite panel and process parameters on the degree of cure and then on the mechanical properties of the adhesive at interface between skin and stringers.